Impact of an antimicrobial resistance control program: pre- and post-training antibiotic use in children with typhoid fever - Elfrida A. Rachmah; Maftuchah Rochmanti; Dwiyanti Puspitasari (Paediatrica Indonesiana, 2016)
Inappropriate use of antibiotics may lead to antimicrobial resistance. In 2012, Dr. Soetomo Hospital conducted training for pediatric residents on the proper use of antibiotics to limit antimicrobial resistance.Objective To evaluate the impact of a rational, antibiotic-use training program for pediatric residents on their antibiotic prescriptions for patients with typhoid fever.Methods A cross-sectional, analytic study was conducted. We collected data from children with typhoid fever who were hospitalized in Dr. Soetomo Hospital, pre- and post-training on antibiotic prescriptions. Children with other known bacterial infections or who were discharged on request were excluded. Antibiotic prescriptions were evaluated using Gyssens algorithm based on the local protocol. Chi-square test was used to compare the quality of antibiotic prescriptions, before (year 2012) and after (year 2013) the training.Results Forty-nine patients with 67 prescriptions in 2012 and 34 patients with 48 prescriptions in 2013 fulfilled the inclusion criteria. Patients’ ages ranged from 1-18 years. Diagnoses of uncomplicated and complicated typhoid were found in 74% and 26% of subjects, respectively. First line (chloramphenicol, thiamphenicol, ampicillin, trimetroprim and sulfametoxazol) and second line (ceftriaxone and cefixime) use were 72% and 28%, respectively. All patients were discharged in good condition. Appropriate use of antibiotics was noted in 61% of subjects in 2012 and in 81% of subjects in 2013 (P=0.036). The most common type of error in 2012 and 2013 was dosage imprecision (25% and 17%, respectively).Conclusion Training on appropriate use of antibiotics significantly improved the quality of antibiotics prescribed in children with typhoid fever in Dr. Soetomo Hospital.